2022
DOI: 10.1186/s12957-021-02461-6
|View full text |Cite
|
Sign up to set email alerts
|

Screening and analysis of RNAs associated with activated memory CD4 and CD8 T cells in liver cancer

Abstract: Background Liver cancer is one of the most common malignant tumors in the world. T cell-mediated antitumor immune response is the basis of liver cancer immunotherapy. Objective To screen and analyze the RNAs associated with activated memory CD4 T cells and CD8 T cells in liver cancer. Methods ESTIMATE was used to calculate the stromal and immune scores of tumor samples, which were downloaded from The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73). In our study, IL1B and ITGA were up-regulated in cervical cancer, while CST7 was down-regulated in cervical cancer, we conducted cell experiments on 3 key genes, and the results showed that downregulation of IL1B and ITGA5 and overexpression of CST7 could reduce the growth and migration ability of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…ITGA5 is a crucial immunotherapy predictive target that is thought to be crucial in the incidence and progression of many cancers (70)(71)(72). CST7 is associated with activation of CD4T and CD8T cells in liver cancer (73). In our study, IL1B and ITGA were up-regulated in cervical cancer, while CST7 was down-regulated in cervical cancer, we conducted cell experiments on 3 key genes, and the results showed that downregulation of IL1B and ITGA5 and overexpression of CST7 could reduce the growth and migration ability of cervical cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in this core network, these three hub DElncRNAs regulated 77% of the DEmRNAs through 24 miRNAs, confirming their importance in the network. Among these 24 miRNAs, miR-23b-3p was reported to be involved in the epithelial-mesenchymal transition (EMT) of HCC by targeting EOMES mRNA [ 40 ], and miR-10a-5p has also been proved to be associated with migration and invasion in HCC cells [ 41 ]. At the same time, the apoptosis-related gene PIM1 [ 42 ], proliferation-related gene CCND1 [ 43 ], migration- and invasion-related gene BMPR2 [ 44 ], and tumor immunocyte infiltration-related gene IFNAR1 also appeared in the core network [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cellular immune response is one of the antitumor immune responses, which is mainly dominated by T lymphocyte subsets. Clinical studies have shown (19): when the body's immune function is enhanced, the proportion of CD8+ T lymphocytes in immune cell subsets increases significantly; while CD8+ T lymphocytes are effector T lymphocytes, which are involved in the body's immune response.During this process, it plays the role of killing antigens, including cancer antigens, which can reflect the cellular immune status of the body (20,21). It has been proved in liver cancer that the number of CD8+ T cells infiltrated in tumor tissue is positively correlated with prognosis, that is, the more CD8+ T cells infiltrated in liver cancer tissue, the…”
Section: Discussionmentioning
confidence: 99%